If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 8)(3x + 24) = 0 Reorder the terms: (8 + 2x)(3x + 24) = 0 Reorder the terms: (8 + 2x)(24 + 3x) = 0 Multiply (8 + 2x) * (24 + 3x) (8(24 + 3x) + 2x * (24 + 3x)) = 0 ((24 * 8 + 3x * 8) + 2x * (24 + 3x)) = 0 ((192 + 24x) + 2x * (24 + 3x)) = 0 (192 + 24x + (24 * 2x + 3x * 2x)) = 0 (192 + 24x + (48x + 6x2)) = 0 Combine like terms: 24x + 48x = 72x (192 + 72x + 6x2) = 0 Solving 192 + 72x + 6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '6'. 6(32 + 12x + x2) = 0 Factor a trinomial. 6((8 + x)(4 + x)) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(8 + x)' equal to zero and attempt to solve: Simplifying 8 + x = 0 Solving 8 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + x = 0 + -8 x = 0 + -8 Combine like terms: 0 + -8 = -8 x = -8 Simplifying x = -8Subproblem 2
Set the factor '(4 + x)' equal to zero and attempt to solve: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4Solution
x = {-8, -4}
| 90+x+34+x+64=180 | | -6x^3+9x^2+6x= | | .5y-4=33.33y-3 | | y-3x=-5y | | 5x+10=5x-10 | | 23b+70=40b-100 | | 12a+95=26a-87 | | a+56=3a+46 | | 3mn^3/14x^2y/9n^4/7x^4y^3 | | 6-2x^2=0 | | 15u+80=71u-88 | | 22s-64=15s+13 | | 2w+82=32w-98 | | ax=7-bx | | 11b+30=30b-84 | | 31m-4=21m+76 | | -6x-42=-35 | | 42f-100=27f-25 | | h+76=2h+23 | | 2/4(x+8)=1/3(x+27) | | (6x-3)+2=5x | | 4k-4k-1=48 | | (3z-8)(z+5)=0 | | -2t+11t+(5+-9)t= | | -1/4+-3/4= | | -72=6w | | kx=-2 | | 4-3(5*0)+2= | | 10x-7+3x=5x+7-8x | | 4x-4=6x+7 | | 5/2x-7=3/4x+14 | | 2+2f=4 |